Analisis Komparatif Laporan Keuangan PT. Wijaya Karya (Persero) Tbk dengan Industri Building Construction yang terdaftar Di Bursa Efek Indonesia Periode 2014-2019 - Dimas Iskandar; Bambang Santoso Marsoem (J-MAS (Jurnal Manajemen dan Sains), 2021)
This paper analyzes the financial performance of PT Wijaya Karya (Persero) Tbk. compared to the total industry based on Financial Ratio Analysis. The data used are the financial statements for the period 2014-2019 which are listed on the Indonesia Stock Exchange as many as 17 companies. Of these, 12 companies had complete financial reports. Thus the industrial data used in the sample in this paper is data from 12 companies. The data analysis method in this research is descriptive statistical analysis and financial ratio analysis. The results of this study are expected to be a benchmark in assessing the financial performance of PT Wijaya Karya Tbk